Konseling Lintas Budaya dan Agama di Sekolah - Muhamad Rifa'i Subhi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2017)
This study aims to determine the form of cross-cultural and religious counseling services in MTs Negeri Yogyakarta 2, as well as the effectiveness of these services in helping students overcome the problem of independence in emotional aspects. This type of research is qualitative field research. The research subjects were grade IX students, who had different cultural and religious backgrounds. The data collection method uses the method of observation and interviews. Data analysis techniques using critical analytical methods. The results showed that MTs Negeri Yogyakarta 2 had implemented cross-cultural and religious counseling services well, and proved to be effective in dealing with students' problems regarding the problem of independence in emotional aspects. This can be shown from the existence of significant changes from students regarding their interactions with peers, as well as their ability to determine future choices in the career field. The data obtained can be formulated into alternative paradigms by counselors or guidance and counseling teachers in providing cross-cultural and religious guidance and counseling services in schools.